Tropes of social becoming along a history or circulation within West Africa and from there to Latin America (2023)
ABSTRACT: Since the turn of the 21st century, the circulation of people from West Africa in and out of the African continent has intensified, turning Latin America into an emergent destination and transit zone. Drawing both from scholarly works and fiction, this article reflects on tropes of social becoming within a history of West African human movement that precedes present day circulation. By tropes of social becoming, I mean narratives around people realizing aspirations, in which scholars, storytellers, literary persons, and the media bring it into existence. While some of the tropes this article addresses seem to stretch to pre-colonial times, others are the product of colonial rule, and yet others emerge in times of structural adjustment. These tropes offer an entry point to understanding how present circulations of Africans in West Africa and Latin America relate to continuity and change.